Congress : its contemporary role - Griffith, Ernest S. (Bombay, 1970)
This book in its original form and the second revised edition were written while the author was Director of the Legis lative Reference Service of Congress. This position imposed certain necessary limitations as to scope. For example, overt recommendations were incompatible with the author's day-to-day work. The author owed a larger loyalty to the confidence which Congress was showing in the impartial character of the Service and in its re nunciation of any attempt at direct influence on policy decisions. There were also obvious restraints as regards specific criticism of Congress. While within its defined scope the book represented an honest analysis and evalua tion of Congress, this analysis was necessarily incomplete. These omissions did not, I believe, affect or distort the main strands as developed or the conclusions drawn therefrom as to the congressional role in the present age. The basic strands remain unaltered.
Keywords: Legislative bodies